1.172. Rozwiąż równania: a) log2 (9 ^ (x – 1) + 7) = 2 + log2 (3 ^ (x – 1) + 1) b) log2 (9 – 2 ^ r) = 25 ^ log2 sqrt(3 – x) c) log2 (25 ^ (x + 1) – 1) = 2 + log2 (5 ^ (x + 3) + 1) d) log6 (3 ^ (x ^ 2) + 1) – log5 (3 ^ (2x ^ 2) + 9) = log6 2

1.172. Rozwiąż równania: a) log2 (9 ^ (x – 1) + 7) = 2 + log2 (3 ^ (x – 1) + 1) b) log2 (9 – 2 ^ r) = 25 ^ log2 sqrt(3 – x) c) log2 (25 ^ (x + 1) – 1) = 2 + log2 (5 ^ (x + 3) + 1) d) log6 (3 ^ (x ^ 2) + 1) – log5 (3 ^ (2x ^ 2) + 9) = log6 2

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz